Short-term therapy with R568 ameliorated secondary hyperparathyroidism but does not prevent aortic valve calcification in uremic rats - Abu-Snieneh, Asmahan; Gurt, Irina; Abedat, Suzan; Lotan, Chaim; Glikson, Michael; Shuvy, Mony (Frontiers in Nephrology, 2024)
IntroductionRenal failure associated aortic valve calcification (AVC) is the result of hyperphosphatemia and hyperparathyroidism. Calcimimetics is an effective tool for management of secondary hyperparathyroidism. Our goal was to evaluate the effect of the medical intervention with calcimimetic R568 on the AVC process.Methods and resultsThe experimental design consisted of administering a uremia-inducing phosphate-enriched diet to rats for six weeks. Rats received a daily R568 injection at different times. Biochemical analysis demonstrated increased urea (34.72 ± 3.57 vs. 5.18 ± 0.15 mmol/L, p<0.05) and creatinine (293.93 ± 79.6 vs. 12.82 ± 1.56 µmol/L, p<0.05). R568 treatment markedly reduced parathyroid hormone (PTH) levels in both treated groups (192.63 ± 26.85, 301.23 ± 101.79 vs. 3570 ± 986.63 pg/mL, p<0.05), with no impact on serum calcium and phosphate. von Kossa staining showed increase in AVC in uremic rats compared to control (1409 ± 159.5 vs. 27.33 ± 25.83, p<0.05). AVC was not affected by R568 in both groups (3343 ± 2462, 1593 ± 792 vs. 1409 ± 159.5, NS). Similarly, the inflammatory marker CD68 was elevated in uremic rats (15592 ± 3792 vs. 181.8 ± 15.29, p<0.01), and was not influenced by R568 treatment (8453 ± 818.5, 9318 ± 2232 vs. 15592 ± 3792, NS). Runt-related transcription factor 2 (Runx2), the regulator of osteoblast differentiation, was upregulated in uremic rats (23186 ± 9226 vs. 3184 ± 2495), that accompanied by elevated levels of Osteopontin (158395 ± 45911 vs. 237.7 ± 81.5, p<0.05) and Osteocalcin (22203 ± 8525 vs. 489.7 ± 200.6, p<0.05). R568 had no impact on osteoblastic markers (Runx2: 21743 ± 3193, 23004 ± 10871 vs. 23186 ± 9226, NS; osteopontin: 57680 ± 19522, 137116 ± 60103 vs. 158395 ± 45911, NS; osteocalcin: 10496 ± 5429, 8522 ± 5031 vs. 22203 ± 8525, NS).ConclusionIn an adenine-induced uremic rat model, we showed that short-term R568 therapy had no effect on AVC. Treatment with R568 decreased PTH levels but had no effect on high phosphate levels. Regression of AVC necessitates not only a decrease in PTH levels, but also a decline in phosphate levels. To achieve improved outcomes, it is advisable to consider administering a combination of R568 with other medications, such as calcium supplements or phosphate binders. Additional studies are required for further evaluation of the potential treatment of chronic kidney disease (CKD)-associated AVC.